Current status of coral reefs in Tioman Island, Peninsular Malaysia - Saad, Shahbudin; Khodzori, Mohd. Fikri Akmal; Salleh, Faris; Mohammad Noor, Normawaty; Yukinori, Mukai (Tubitak, 2017)
The present study aimed to determine the current status of corals using the coral video transect (CVT) method in the east coast, west coast, and isolated areas of Tioman Island, Peninsular Malaysia. A total of 65 genera from 21 families of corals were identified, from which the scleractinian corals of Acropora, Montipora, and Porites were dominant in the coral assemblages. Nine reef sites were categorised as having ‘good’ (51.4%–60.3%) coral condition and four reef sites as having ‘fair’ (37.6%–49.2%) coral condition. This study concluded that the reefs around Tioman Island were in ‘good’ average coral condition and have high generic diversity with mixed coral morphological structures. The east coast and isolated areas had better live coral cover compared to the west coast area due to less coastal development and human impacts.